2008
DOI: 10.3748/wjg.14.3710
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus DNA is more powerful than HBeAg in predicting peripheral T-lymphocyte subpopulations in chronic HBV-infected individuals with normal liver function tests

Abstract: AIM:To investigate the peripheral T-lymphocyte subpopulation profile, and its correlations with hepatitis B virus (HBV) replication level in chronic HBV-infected (CHI) individuals with normal liver function tests (LFTs). METHODS: Frequencies of T-lymphocyte subpopulations in peripheral blood were measured by flow cytometry in 216 CHI individuals. HBV markers were detected with ELISA. Serum HBV DNA load was assessed with quantitative real-time PCR. Information of age at HBV infection, and maternal HBV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Few studies have had the opportunity to evaluate the impact of HBsAg on the absolute CD4 count using a wide range of CD4 values as previous studies have assessed patients initiating antiretroviral therapy (usually with CD4 <200 cells/mm 3 ). Some of these studies have reported an association between HBsAg and CD4 count while others have not (1315). However these previous studies have been focused on ART initiators which may mask an association between CD4 count and CH-B and are susceptible to confounding by an unmeasured factor influencing both CH-B risk and timing of presentation for antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have had the opportunity to evaluate the impact of HBsAg on the absolute CD4 count using a wide range of CD4 values as previous studies have assessed patients initiating antiretroviral therapy (usually with CD4 <200 cells/mm 3 ). Some of these studies have reported an association between HBsAg and CD4 count while others have not (1315). However these previous studies have been focused on ART initiators which may mask an association between CD4 count and CH-B and are susceptible to confounding by an unmeasured factor influencing both CH-B risk and timing of presentation for antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on HBV mono-infection support the hypothesis that HBV is associated with lower CD4+ T-cell counts. In a Thai study, HBV mono-infected individuals had lower CD4+ T-cells compared to HBsAg-negative subjects [13]; this association was strongest in those with high HBV DNA, detectable HBeAg, and HBV infection before the age of 20. A study of pregnant Indian women found that CD4+ T-cell counts were lower in 25 women with HBsAg compared to nearly 1,100 women without HBsAg [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the patients infected with genotype C need to be carefully monitored to assess their future clinical outcomes. Particularly, sub-genotype C1 is documented to have an increased tendency for the development of cirrhosis and hepatocellular carcinoma (HCC), especially in patients over 50 years of age [43][44][45]. On the other hand, genotype B patients have higher rates of HBeAg seroconversion, and HCC has been detected in younger patients [43,[46][47].…”
Section: Discussionmentioning
confidence: 99%